Losses in a high-temperature superconductor exposed to AC and DC transport currents and magnetic fields. - Schonborg, N. (IEEE Transactions on applied superconductivity)
Summary form only given, as follows. The development of high-temperature superconductors (HTSs) is for the moment intensive and it is likely that HTSs will be used in different electric devices in a few years. In some of these devices that conductor will be exposed to both AC and DC transport currents and magnetic fields. In the design of electric devices, the power loss is indeed one of the most important parameters. Therefore there is a need of models that predict the power loss in an HTS under application-like conditions. In this paper, the authors present a semi-empirical model including a transport current and an applied magnetic field with both AC and DC components. The semi-empirical model is mainly based on the critical state theory. The results of the model are compared and found to be in good agreement with experimental results obtained with a calorimetric experimental set-up. The power loss was measured on a multi-filamentary Bi-2223 tape as function of transport current and applied magnetic field at a fixed temperature and frequency